Kinematic analysis of roundhouse kick according to the stance position - Estevan, I.; Jandacka, D.; Farana, R.; Falcó, C. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The stance position has been pointed out as an important factor that can potentially affect the kick performance, so the stance position can be seen as a constraint for the execution. The aim of this study was to compare kinematic variables in some main instants during the roundhouse kick in taekwondo according to three stance positions (0º, 45º, 90º). Nine experienced athletes participated in the study. Kinematic analysis was measured by two 3D force plates and an eight-camera motion capture system. Data analyses were processed using Visual 3D software. Signifficant differences in kinematic data were found at the beggining of the kick; these differences disappear at the end of the kick. Athletes are able to adapt their technique even if the stance position is different.